2023
DOI: 10.3389/fphys.2023.1056354
|View full text |Cite
|
Sign up to set email alerts
|

Cortex-specific transcriptome profiling reveals upregulation of interferon-regulated genes after deeper cerebral hypoperfusion in mice

Abstract: Background: Chronic cerebral hypoperfusion (CCH) is commonly accompanied by brain injury and glial activation. In addition to white matter lesions, the intensity of CCH greatly affects the degree of gray matter damage. However, little is understood about the underlying molecular mechanisms related to cortical lesions and glial activation following hypoperfusion. Efforts to investigate the relationship between neuropathological alternations and gene expression changes support a role for identifying novel molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 77 publications
(93 reference statements)
3
6
0
Order By: Relevance
“…Based on our results, as well as those of previous studies [ 15 ], we successfully established the 0.16/0.18 mm BCAS hypoperfusion model for gray matter lesions, with microglia manifesting a state of neuroinflammatory activation in the cerebral cortex. We then utilized both RNA-seq and ATAC-seq to study the effect of chromatin accessibility on gene expression as a whole, in order to investigate the molecular mechanics of CCH.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Based on our results, as well as those of previous studies [ 15 ], we successfully established the 0.16/0.18 mm BCAS hypoperfusion model for gray matter lesions, with microglia manifesting a state of neuroinflammatory activation in the cerebral cortex. We then utilized both RNA-seq and ATAC-seq to study the effect of chromatin accessibility on gene expression as a whole, in order to investigate the molecular mechanics of CCH.…”
Section: Introductionsupporting
confidence: 66%
“…Thus, it can be concluded that BCAS hypoperfusion resulting from 0.16 mm stenosis can cause clearly evident histological injury. In our previous work, we found activation of microglia occurred mostly in areas of neuronal injury, including the cerebral cortex on the 0.16 mm stenosis side of BCAS mice [ 15 ]. Microglia, as the primary innate immune cells and important cellular mediators in the brain, play an important role in neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations